Media Pembelajaran Pengenalan Alat Transportasi, Musik, dan Benda di Sekolah bagi Siswa Tunarungu Sekolah Dasar - Septiana, R; Al Irsyadi, F Y (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2021)
A remarkable school – B (SLB) YRTRW Surakarta is a spesial school for children with special school for children with special needs to help provide education. According to a survey of SLB-B YRTRW Surakarta, it is difficult for students to get the names of objects right anf there are still mistakes, and it is also difficult for students to play because the learing methods are less interesting and therefore not focus on the material presented by teachers. An alternative or solution is to provide the learning media in the form of applications. The appication is called BELMA (together learning) abaout the introduction of transportation tools, Musical Instruments, and objects in the school environment for fourth-grade elementary school students. The founding of the media of education is a method for observation, analysis or problem identification, and interviews. The result of research based on questionnaires are 87.871%, and this application can thus help the learning process. The purpose of this study is to be expected to help both tearchers and students in the learning process in class so that students can be quick to understand and enthusiastic about material delivery.